ANALISIS FAKTOR YANG MEMPENGARUHI PROGRAM PMTCT DALAM STRATEGI MENURUNKAN ANGKA HIV DI KABUPATEN SITUBONDO: ANALISIS FAKTOR YANG MEMPENGARUHI PROGRAM PMTCT DALAM STRATEGI MENURUNKAN ANGKA HIV DI KABUPATEN SITUBONDO - Reffita, Lea Ingne (WELL BEING, 2020)
PMTCT is a government program to prevent HIV infection from mothers who are transmitted to their babies. An increasing number of women infected with HIV are getting higher. along with the increase in the number of men who have unprotected sexual relations and through injecting drugs, who will transmit HIV to their sexual partners. The purpose of this study is to explore the implementation of the PMTCT program in Situbondo Regency. The research design used is qualitative research with a phenomenological approach. Data collection uses indepth interview techniques with semi-structured questions. The sampling technique in this study used purposive sampling with a sample of 8 informants from 17 existing informants. The results of the study show that the process of implementing the PMTCT program influences the development of the PMTCT program each year and will have a positive impact both for health workers and for women who are pregnant. In the process of implementing the PMTCT program, it is influenced by several factors, among others there are factors that support the process of implementing the PMTCT program as well as those that inhibit. Of these inhibiting factors, a number of special efforts and strategies were undertaken to support the implementation of the PMTCT program. In the process of implementing the PMTCT program there are some hopes to support the course of the PMTCT program, namely the existence of a poly VCT to improve this service in the future. Based on this research further research is needed on the process of implementing the PMTCT program